2013
DOI: 10.1371/journal.pone.0069079
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of SPARC Expression Inhibits the Invasion of Human Trophoblast Cells In Vitro

Abstract: Successful pregnancy depends on the precise regulation of extravilloustrophoblast (EVT) invasion into the uterine decidua. SPARC (secreted protein acidic and rich in cysteine) is a matricellular glycoprotein that plays critical roles in the pathologies associated with obesity and diabetes, as well as tumorigenesis. The objective of this study was to investigate the role of SPARC in the process of trophoblast invasion which shares many similarities with tumor cell invasion. By Western blot, higher expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 45 publications
5
8
0
Order By: Relevance
“… 36 Jiang et al showed that SPARC depletion upregulated the expression of IGFBP4, which promoted the invasion of JEG-3. 29 The above results were consistent with our study, strongly indicating that hub genes mostly participated in tumour proliferation and invasion.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“… 36 Jiang et al showed that SPARC depletion upregulated the expression of IGFBP4, which promoted the invasion of JEG-3. 29 The above results were consistent with our study, strongly indicating that hub genes mostly participated in tumour proliferation and invasion.…”
Section: Discussionsupporting
confidence: 92%
“… 28 Jiang et al found that the mRNA and protein expression of SPARC was downregulated in JEG-3 cells compared with HTR-8/SVneo cells. 29 Furthermore, miRNAs in cancer were the primary pathway for DEG enrichment. This result suggested that miRNAs may play a vital role in mediating choriocarcinoma progression.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that human placenta villi could express and secrete SPARC [27], suggesting that levels of SPARC may be affected by gestational age. However, in our study the subjects in GDM group and control group had similar gestational age, around 26 weeks of gestation and it has been shown that circulating levels of SPARC mainly come from adipose tissue [11], therefore, the differences in circulating levels of SPARC in GDM patients and controls may not be caused by gestational age.…”
Section: Discussionmentioning
confidence: 99%
“…So far there are limited studies on SPARC and diabetic subjects, and the findings are consistent with our results: levels of SPARC are significantly elevated in T2DM patients compared with normal controls in Chinese and Japanese populations [14] , [26] . A recent study showed that human placenta villi could express and secrete SPARC [27] , suggesting that levels of SPARC may be affected by gestational age. However, in our study the subjects in GDM group and control group had similar gestational age, around 26 weeks of gestation and it has been shown that circulating levels of SPARC mainly come from adipose tissue [11] , therefore, the differences in circulating levels of SPARC in GDM patients and controls may not be caused by gestational age.…”
Section: Discussionmentioning
confidence: 99%
“…Following blastocyst adhesion, trophoblast cells differentiate and acquire the invasive phenotype [ 154 ]. The role of PGs in facilitating trophoblast invasion is largely unknown; however, several evidences indicate its involvement in this process.…”
Section: Role Of Pgs In Trophoblast Invasionmentioning
confidence: 99%